2009
DOI: 10.1097/nan.0b013e3181bd5668
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complication Rates and Reasons for Nonelective Removal of PICCs in Neonatal Intensive Care Unit Preterm Infants

Abstract: The aim of this study was to analyze the complication rates of peripherally inserted central catheters (PICCs) in neonatal intensive care units (NICUs) and to study the risk factors associated with the nonelective removal of PICCs. One hundred four premature infants were enrolled. Ninety-one PICCs were removed electively. The complications rate was 31.73%, most of which was phlebitis. All patients were further divided into 2 groups: elective removal (ER) and nonelective removal (non-ER). This study reinforces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
2
10
0
9
Order By: Relevance
“…The findings on association between the selected vein and the incidence of non-elective removal are similar to this study's results (13) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings on association between the selected vein and the incidence of non-elective removal are similar to this study's results (13) .…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the incidence of non-elective removal was similar to other studies conducted in different facilities, which ranged from 31.7% (13) to 47.7% (14) . However, the present study found that the main reasons for non-elective removal were different among the three possible segments of PICC insertion.…”
Section: Discussionsupporting
confidence: 75%
“…[2][3][4]9 As a result, efforts have been conducted in many NICUs to limit rates of these complications and their associated morbidity and mortality. Most notably, dramatic success has been reported with both local and regional efforts to reduce central line-associated bloodstream infections.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies estimate that catheter-related complications may occur in up to 30% of PICCs placed in the NICU. [2][3][4] Similar NICU-specific data, however, are not available for PINCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al () investigated the risk factors associated with the nonelective removal of PICCs in 104 preterm infants (mean gestational age of 30.5 weeks). The authors reported that in the elective removal group 85 (93.5%) catheter tips were positioned at the junction of superior vena cava and right atrium, which was significantly higher than in the nonelective removal group ( p < 0.01).…”
Section: Introductionmentioning
confidence: 99%